1990
DOI: 10.1159/000243148
|View full text |Cite
|
Sign up to set email alerts
|

Free Cortisol of Human Plasma in the First Three Months of Life

Abstract: Total cortisol as well as percentage and absolute free cortisol values were determined in 75 full-term, 88 premature and 38 small-for-age (born at term) infants in the first 3 months of life. Equilibrium dialysis and radioimmunoassay were used to estimate the percentage value of the unbound fraction and the value of total cortisol from which absolute free cortisol level was calculated, respectively. A systematic decrease in the free cortisol value was observed in all the three groups of infants during the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 19 publications
4
20
1
Order By: Relevance
“…Any explanation for this low value must take into account the fact »that cortisol displays no circadian rhythm at this age. These low serum cortisol concentrations in neonates are in agreement with the results of Rockicki et al (6) and Forest (9). The work of Struckmeyer & Haid (8) showed no clear trend with age^ whereas Lashansky et al (7) found distinctly higher concentrations in infants.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Any explanation for this low value must take into account the fact »that cortisol displays no circadian rhythm at this age. These low serum cortisol concentrations in neonates are in agreement with the results of Rockicki et al (6) and Forest (9). The work of Struckmeyer & Haid (8) showed no clear trend with age^ whereas Lashansky et al (7) found distinctly higher concentrations in infants.…”
Section: Discussionsupporting
confidence: 93%
“…Those childhood reference ranges that have appeared in the literature are shown in table 4 (6)(7)(8)(9). These data are not comparable with the present results for the following reasons:…”
Section: Discussionmentioning
confidence: 99%
“…Full-term neonates exhibited significantly higher salivary cortisol concentrations than healthy preterm neonates. In contrast, Rokicki et al [31]observed that free plasma cortisol concentrations in premature newborns at 3–5 days of life exceeded the values in full-term neonates, but their study protocol did not consider temporal changes of adrenal secretory activity and blood samples were randomly collected throughout the day. However, our data indicate that maxima of cortisol secretion already characterize adrenal activity in premature neonates and that the amplitude of these surges increases in the postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy full-term neonates have mean serum cortisol concentrations of 339 nmol/l at the age of 0–6 h [23], and preterm infants at the same age have mean serum cortisol concentrations of 400 nmol/l [23]. During the first day of life, the serum cortisol concentration gradually declines [24, 25], and at the age of 3–10 days, average levels of 165–219 nmol/l in preterm, and 171–250 nmol/l in full-term infants have been measured [21, 25].…”
Section: Discussionmentioning
confidence: 99%